2013
DOI: 10.2485/jhtb.22.445
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Cement Lines

Abstract: Bone remodeling is achieved through the resorptive activity of osteoclasts and the synthetic activity of osteoblast and it continues throughout life. Cement lines are formed by osteoblasts and are recognized between old and new bone. However, the detailed structure of cement lines has still not been clarified. The present study researched the ultrastructure of cement lines in a ferret femur using light microscopy (LM), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). On LM, many r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On both periosteal and endocortical surfaces thickening of bone was radiologically observed in the transverse radiolucent linear zone. A border between the original lateral cortex and the newly formed endosteal lamellar bone may be a type of the “cement line”, but it is primarily a term for formation of secondary osteon ( Skedros et al, 2005 ; Okada et al, 2013 ). It seems, in this case, endosteal lamellar bone formation is modeling-based formation, started with resorption of the lateral cortex, but not remodeling-based formation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On both periosteal and endocortical surfaces thickening of bone was radiologically observed in the transverse radiolucent linear zone. A border between the original lateral cortex and the newly formed endosteal lamellar bone may be a type of the “cement line”, but it is primarily a term for formation of secondary osteon ( Skedros et al, 2005 ; Okada et al, 2013 ). It seems, in this case, endosteal lamellar bone formation is modeling-based formation, started with resorption of the lateral cortex, but not remodeling-based formation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…That there should be a gap in the spicule–ZCC interface, a result of the removal of the mineral phase from decalcification, requires further discussion in the context of the cement line of secondary osteons. In the latter, studies have shown that the cement line is a hypermineralised zone and collagen deficient (Okada et al, 2013; Hosseini et al, 1999; Skedros et al, 2005), with significantly higher Ca/P molar ratios than bone (Schaffler et al, 1987). Thus with the removal of this mineral phase, a void would result, and this is consistent with previous SEM studies of bone tissue where the cement line and lamellae boundaries were enhanced following citric acid exposure (Congiu & Pazzaglia, 2011) or the collagen fibrils exposed following complete demineralisation with HCL acid (Traini et al, 2005).…”
Section: Discussionmentioning
confidence: 99%